The role of Zinc Intake in Serotonin and Cortisol Level in Patient with Depression - Tanjung Ayu Sumekar; Innawati Jusup; Natalia Dewi Wardani; Titis Hadiati; Mohammad Sulchan; Alifiati Fitrikasari (Faculty of Medicine, Universitas Diponegoro, 2022)
Background: Low zinc levels affects the relationship between the glutamatergic and serotonergic systems in major depressive disorders that cause stress and inflammation. Decreased zinc in the hippocampus can activates the HPA axis associated with an increase in cortisol. Several studies documented the relationship between zinc and clinical depression, however further research including biological measurements is needed to support these studies.Objective: To observe the correlation between zinc intake with serotonin and cortisol serum in patient with depressionMethods: This was an observational study with cross sectional design. Subjects were patients with depression who came to Dr. Kariadi Hospital, Tugurejo Hospital, Diponegoro National Hospital and Permata Medika Hospital met the inclusion and exclusion criteria. The food frequency questionnaire (FFQ) was used to assess daily zinc intake. The levels of serum serotonin and cortisol were measured using ELISA technique.Results: Of the 53 subjects, there was significant correlation between zinc intake with serotonin serum level (p=0,038), however there was no correlation between zinc intake with cortisol serum level (p=0,845)Conclusion: The higher zinc intake the higher serotonin serum level, however there was no correlation between zinc intake with cortisol serum level in patients with depression.